2014
DOI: 10.1155/2014/535929
|View full text |Cite
|
Sign up to set email alerts
|

AnEx VivoModel in Human Femoral Heads for Histopathological Study and Resonance Frequency Analysis of Dental Implant Primary Stability

Abstract: Objective. This study was designed to explore relationships of resonance frequency analysis (RFA)—assessed implant stability (ISQ values) with bone morphometric parameters and bone quality in an ex vivo model of dental implants placed in human femoral heads and to evaluate the usefulness of this model for dental implant studies. Material and Methods. This ex vivo study included femoral heads from 17 patients undergoing surgery for femoral neck fracture due to osteoporosis (OP) (n = 7) or for total prosthesis j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Regarding the osteocyte count, no statistical differences were observed between the different regions evaluated (P ¼ 02946). Herna ´ndez-Corte ´s et al (2014) 24 also used osteocyte count as an indicator to assess bone quality. However, the authors did not find statistically significant differences in the amount of osteocytes in the femoral head with osteoporosis and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the osteocyte count, no statistical differences were observed between the different regions evaluated (P ¼ 02946). Herna ´ndez-Corte ´s et al (2014) 24 also used osteocyte count as an indicator to assess bone quality. However, the authors did not find statistically significant differences in the amount of osteocytes in the femoral head with osteoporosis and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not an applicable feature in the routine clinic, histometry is considered the gold standard to assess bone quality 24,25 . Trisi and Rao (1999) 10 found a positive correlation between the clinical and histomorphometric evaluation of bone quality after implant insertion in 56 patients, mainly in the differentiation of bone types I and IV.…”
Section: Discussionmentioning
confidence: 99%
“…Bone grafting materials used for socket augmentation have influenced bone quality as well 9 . Changes in bone quality and quantity have a significant influence on performance of implant therapy 10 …”
mentioning
confidence: 99%
“…Moreover, the study designs of the above-motioned studies differ in their selection of animal models, surgical techniques, and implant types. Similarly, Hernández-Cortés et al found no associations between initial ISQ values and histomorphometric results in human femoral heads [ 40 ]. This is because primary implant stability measured by ISQ values was significantly correlated with the cortical bone thickness, but not with bone histomorphometric parameters [ 23 , 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%